East Asia Decentralizes. (World Bank e-Library., 2005)
The past two decades have witnessed a fundamental transformation in the structure of government across East Asia. Prior to 1990 most East Asian countries were highly centralized; today, decentralization is ubiquitous throughout the region. From China to Thailand, sub-national governments are now responsible for the delivery of critical services and account for a significant proportion of total public expenditure. In just two decades, local and regional authorities have emerged as the organizational fulcrum on which much of the weight of development now falls. East Asia Decentralizes is the first attempt to look systematically at this phenomenon throughout East Asia. It is broken into four main sections. Chapters 1 and 2 provide an overview of the intergovernmental structures and frameworks that have emerged thus far, assess the status of the decentralization process, and identify key reform challenges for the future. Chapters 3-7 examine various dimensions of local and intergovernmental finance: sub-national borrowing; local revenues; public expenditure management; and the impact of the process on inter-regional equity and poverty reduction. The management of human resources is also covered here. Chapters 8-10 focus on the impact of decentralization on investment and service-delivery in three key sectors: health, education and basic infrastructure. The final two chapters (11-12) look at issues connected with local accountability and community driven development.